Artificial Intelligence in Education Management: A Systematic Review of Decision Support Systems for Inclusive Education - Jamaludin, Haris (University of Science and Computer Technology, 2025)
This study examines the integration of artificial intelligence (AI) into education management systems, focusing on decision-support mechanisms for inclusive education. Through a systematic literature review of publications from 2019 to 2024, this research analyzes how AI technologies transform educational management practices and inform strategic decision-making. The findings reveal that AI-driven management systems significantly enhance resource allocation, personalized learning path creation, and inclusive education monitoring through advanced data analytics and predictive modeling. However, implementation challenges include data integration complexities, staff training requirements, and ethical considerations in algorithmic decision-making. The study identifies critical success factors for AI adoption in educational management, including leadership commitment, technological infrastructure, and stakeholder engagement. This research contributes to management science by providing a framework for AI implementation in educational institutions. It offers practical insights for education managers, policymakers, and technology developers seeking to leverage AI for inclusive education management.